EFEKTIVITAS PEMBERIAN TERAPI FOOT MASSAGE DAN AROMATERAPI TERHADAP PENURUNAN TINGKAT KELETIHAN PADA PASIEN YANG SEDANG MENJALANI HEMODIALISIS - Mandahimas Khoirul Ummah; Dyah Rivani; Agus Rismanta (Universitas 'Aisyiyah Surakarta, 2025)
Chronic Kidney Disease (CKD) is a condition in which the kidneys are damaged and unable to filter blood effectively. One of the common treatment options for managing CKD is hemodialysis. However, long-term hemodialysis can lead to a decreased quality of life, with fatigue being a frequently reported complaint among patients. To address this fatigue, complementary therapies such as foot massage and aromatherapy can be administered. This study aims to examine the effect of a combination of foot massage and aromatherapy on reducing fatigue levels in patients with chronic kidney failure undergoing hemodialysis. The study employed a case study design using the Functional Assessment of Chronic Illness Therapy (FACIT) as the measurement instrument. The intervention was conducted over 8 days, with each session lasting 15 minutes, and took place during hemodialysis either in the hospital or at home with support from family members. Evaluations were conducted on days 1, 5, and 8. The results showed a reduction in fatigue levels, with an initial score of 11 (severe category), increasing to 15 (still severe) on day 5, and 20 (moderate category) on day 8. These findings indicate that the combination of foot massage and aromatherapy can effectively reduce fatigue in patients undergoing hemodialysis. This intervention may be considered by nurses as a non-pharmacological approach to enhance patient comfort